Adenoma pleomórfico de glândulas salivares menores: investigação do potencial neoplásico baseado na apoptose, atividade mucosecretora e proliferação celular - Ferreira, Jean Carlos Barbosa (2014)
Pleomorphic adenoma (PA) is the most common salivary gland tumor, however its etiopathogenesis is unclear, as well as your neoplastic potential. Studies have already been done investigating apoptosis, mucosecretory activity and proliferation cellular, although these studies are controversial. The aim of this study was to investigate the neoplastic potential of the PA of minor oral salivary glands measured by apoptosis (Bcl-2, Bax and p53), mucosecretory activity (MUC1), and cellular proliferation (Ki-67). Thirty-one cases of PA of the oral cavity and 4 controls (C) taken from normal oral minor salivary glands were analyzed by immunohistochemistry technique. The proteins were detected utilizing a semi-quantitative method (scores) as follows: (-) negative ≤ 5%, (+) low 6–25%, (++) moderate 26–50% and (+++) high >50% of positive tumour cells. The apoptotic indices were evaluated by the ratio Bcl-2/Bax. Non-parametric comparison and correlation tests were used for analysis. The data showed high staining of anti-apoptotic protein Bcl-2 in both groups (PA= 57.9%; C=67.7%) and an expression significantly lower of pro-apoptotic protein Bax (PA=22.7%; C=97.7%) and MUC1 (PA=14%; C=82.3%) in PA than in C (p<0.001). On the other hand, we observed a similar expression of Ki-67 and p53 proteins (≤ 5%) in both PA and C. In PA, only 2 cases showed the ratio Bcl-2/Bax <1. There was no difference in cellular expression with regard to clinical variables clinical and outcome (p>0.05). The neoplastic potential of PA can be associated with an imbalance in apoptotic processes and a lower index of proliferation cellular and that the mucosecretory activity does not play a significant role in primary PA.